Early testing on S1 lines of black corn (Zea mays L.) from the Ecuadorian highlands - Merino, Jorge; Viera, William; Garófalo, Javier; Mejía, Paúl; Sánchez, Víctor (Manglar, 2022)
Maize (Zea mays L.) germplasm from the Ecuadorian Higlands has low tolerance to inbreeding especially in starchy cultivars. To create competitive varieties at the commercial level it is necessary to identify outstanding progenitor lines by early testing. The purpose of this research was to evaluate the yield potential of S1 lines of black corn by early testing. The experiment was conducted at the “Tunshi” Experiment Station, Licto parish, Chimborazo province, Ecuador using a complete random block design with four replications. Twenty-four treatments were evaluated, each consisting of an S1 line of black corn. Agronomic traits were registered and the percentage of inbreeding depression was calculated. The lines presented statistical differences (P ≤ 0.05) in the variables days to male and female flowering, plant height, ear height, leaf disease, ear length, weight of 100 kernels and grain yield. All the variables showed inbreeding depression, except days to male flowering, which presented a low increase. Lines 16, 15 and 22 were the most productive with yields of 2.00; 2.08 and 1.95 t ha-1 respectively. These results allow to select lines with less depressive effects on yield produced by inbreeding, and to continue with the improvement processes of black maize.